Biomimetic Guided Bi2WO6/Bi2O3 Vertical Heterojunction with Controllable Microstructure for Efficient Photocatalysis - Yuanbo Sun; Ziang Jia; Ning Wan; Wei Feng (Molecules, 2023)
To bridge the technical gap of heterojunction induction control in conventional semiconductor photocatalysts, a method of regulating the growth of heterojunctions utilizing biomimetic structures was designed to prepare a series of Bi2WO6/Bi2O3 vertical heterojunction nanocomposites for the disposal of environmentally hazardous tetracycline wastewater difficult to degrade by conventional microbial techniques. Porous Bi2O3 precursors with high-energy crystalline (110) dominant growth were produced using the sunflower straw bio-template technique (SSBT). Bi2WO6 with a (131) plane grew preferentially into 2.8 to 4 nm pieces on the (110) plane of Bi2O3, causing a significant density reduction between Bi2WO6 pieces and a dimensional decrease in the agglomerated Bi2WO6 spheres from 3 μm to 700 nm since Bi2WO6 grew on the structure of the biomimetic Bi2O3. The optimal 1:8 Bi2WO6/Bi2O3 coupling catalyst was obtained via adapting the ratio of the two semiconductors, and the coupling ratio of 1:8 minimized the adverse effects of the overgrowth of Bi2WO6 on degradation performance by securing the quantity of vertical heterojunctions. The material degradation reaction energy barrier and bandgap were significantly reduced by the presence of a large number of vertical heterojunction structures, resulting in a material with lower impedance and higher electron–hole separation efficiency; thus, the degradation efficiency of 1:8 Bi2WO6/Bi2O3 for tetracycline hydrochloride reached 99% within 60 min. In conclusion, this study not only successfully synthesized a novel photocatalyst with potential applications in water pollution remediation but also introduced a pioneering approach for semiconductor-driven synthesis.